Os saberes da experiência: a importância do programa residência pedagógica na formação docente - Oliveira, Camila Faustino de (Universidade Federal de São Carlos, 2023)
This work aims to reflect on the importance of experiential knowledge and how the Pedagogical Residency Program contributes to teacher education through the practices and experiences it provides to its student scholars. This reflection is based on a narrative research approach, where the author of this work uses an autobiographical narrative to recount her experiences between the years 2019 and 2022, a period in which she participated in mandatory supervised internship courses and the Pedagogical Residency Program, and how each of these experiences was also crucial to her professional development. Through the theoretical support of authors, the aim is to understand what experiential knowledge is and what its contributions are during the teacher education process. In conjunction with the narrative, the aim is to demonstrate that, in addition to traditional internships, the Pedagogical Residency Program can be a valuable source of learning and formative experience.
Knowledge from experience: the importance of the programa residência pedagógica in teacher training
Saber a partir de la experiencia: la importancia del programa residencia pedagógica en la formación docente
Keywords: Programa Residência Pedagógica; Estágio Supervisionado Obrigatório; Saberes Docentes; Saberes Experienciais; Teaching Knowledge; Experiential Knowledge; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM